Remote working, technostress and well-being during Covid-19 - a generational perspective - Sampaio, Rafaela Lawisch (2022)
The quick change to remote work during the Covid-19 crisis increased technology usage, impacting employees' well-being. The collective report analyzes the relationship between remote work, technostress, and well-being during Covid-19 using the JDR-model. The present report will explore the same variables through a generational perspective as intergenerational characteristics can influence the individual's responses to historical events. Using three surveys, the 426 participants were divided into four generations based on their current age. Significant differences were found, especially between the younger generations. The findings show the importance of closer analysis between generations to avoid stereotype biases and promote better organization management.